Group 4 ITI Consensus Report: Risks and biologic complications associated with implant dentistry. (17th October 2018) - Heitz‐Mayfield, Lisa J.; Aaboe, Merete; Araujo, Mauricio; Carrión, Juan B.; Cavalcanti, Raffaele; Cionca, Norbert; Cochran, David; Darby, Ivan; Funakoshi, Eiji; Gierthmuehlen, Petra C.; Hashim, Dena; Jahangiri, Leila; et al.
Abstract: Objectives: The aim of Working Group 4 was to address topics related to biologic risks and complications associated with implant dentistry. Focused questions on (a) diagnosis of peri‐implantitis, (b) complications associated with implants in augmented sites, (c) outcomes following treatment of peri‐implantitis, and (d) implant therapy in geriatric patients and/or patients with systemic diseases were addressed. Materials and methods: Four systematic reviews formed the basis for discussion in Group 4. Participants developed statements and recommendations determined by group consensus based on the findings of the systematic reviews. These were then presented and accepted following further discussion and modifications as required by the plenary. Results: Bleeding on probing (BOP) alone is insufficient for the diagnosis of peri‐implantitis. The positive predictive value of BOP alone for the diagnosis of peri‐implantitis varies and is dependent on the prevalence of peri‐implantitis within the population. For patients with implants in augmented sites, the prevalence of peri‐implantitis and implant loss is low over the medium to long term. Peri‐implantitis treatment protocols which include individualized supportive care result in high survival of implants after 5 years with about three‐quarters of implants still present. Advanced age alone is not a contraindication for implant therapy. Implant placement in patients with cancer receiving high‐dose antiresorptive therapy is contraindicated due to the associated high risk for complications. Conclusions: Diagnosis of peri‐implantitis requires the presence of BOP as well as progressive bone loss. Prevalence of peri‐implantitis for implants in augmented sites is low. Peri‐implantitis treatment should be followed by individualized supportive care. Implant therapy for geriatric patients is not contraindicated; however, comorbidities and autonomy should be considered.